Mucilage extracted from Chilean papaya seeds is enriched with homogalacturonan domains - Sanhueza, Dayan; Sepúlveda-Orellana, Pablo; Salazar-Carrasco, Alejandra; Zúñiga, Sebastian; Herrera, Raúl; Moya-León, María Alejandra; Saez-Aguayo, Susana (Frontiers in Plant Science, 2024)
Chilean papaya, also known as mountain papaya (Vasconcellea pubescens), is a fruit valued for its nutritional value and pleasant fragrance. The oblong fruit, featuring five ridges and a seed-filled mucilage cavity, is typically consumed cooked due to its high protease content. The mucilage and the seeds are usually discarded as byproducts. This study analyzed the biochemical composition of mountain papaya seed mucilage using methods such as HPAEC and immunolabeling. Results revealed that papaya seeds yield nearly 20% of their weight in mucilage polysaccharides, which can be separated into soluble and adherent layers. The mucilage exhibited a high proportion of acidic sugars, indicating that homogalacturonan (HG) is the predominant domain. It also contained other domains like rhamnogalacturonan-I (RG-I) and hemicelluloses, predominantly xyloglucan. The HG-rich mucilage, currently considered waste, emerges as a promising source of polysaccharides, indicating its multifaceted utility in various industrial applications.